Pengaruh Perencanaan Pajak dan Beban Pajak Tangguhan terhadap Manajemen Laba - Fredy Rankcore; Nyimas Wardatul Afiqoh (Universitas Muhammadiyah Gresik, 2023)
This study aims to determine the influence of tax planning and deferred tax expense on earnings management at manufacturing companies in the food and beverage sub-sector listed on the BEI (Indonesia Stock Exchange) in 2018-2021. This research uses quantitative methods and uses secondary data as a source of data. The sampling technique used purposive sampling technique and obtained 19 company samples. The data analysis technique used us multiple linear regression analysis. The results show that tax planning with a proxy tax retention rate (TRR) has a significant effect on earnings management. Deferred tax expense proxied by deferred tax expense (DTE) affect on earnings management.